A Model With a Collaborative Approach for the Operational Management of the Supply Chain - Acevedo-Urquiaga, Ana Julia; Sablón-Cossío, Neyfe; Acevedo-Suárez, José Antonio; Urquiaga-Rodríguez, Ana Julia (International Journal of Industrial Engineering and Management, 2021)
The implementation of collaborative approaches in supply chains is an objective of many companies. The proposal of this work is to present a model that favors horizontal integration at the tactical-operational level of the supply chain. The model is based in the principles of logistics flow management; and in the balance of demand, supplies, capacities and stocks. The main contribution of the research is the practical application of collaborative planning as a daily tool for integration between all supply chain echelons. The results obtained in the case studies show that this type of approach improve the efficiency and effectiveness of the logistics system. Article history: Received (November 08, 2020); Revised (February 13, 2021); Accepted (February 17, 2021); Published online (February 26, 2021)